Analysis of Intestinal Mucosal Immunoglobulin A in Sprague Dawley Rats Supplemented with Tempeh - SUSAN SOKA; ANTONIUS SUWANTO; IMAN RUSMANA; DONDIN SAJUTHI; DIAH ISKANDRIATI; KATHARINA JESSICA (Bogor Agricultural University, Indonesia, 2015)
Tempeh is a well-known Indonesian fermented food made from soybean. During the fermentation process, microorganisms play an important role in the flavor, texture, and nutritional quality of tempeh. Tempeh has been show to have immuno-modulatory and immune-stimulating properties that may also be caused by the microorganisms in tempeh as they interact between the microbial population in the intestinal tract. The objective of this study was to quantify IgA gene expression at both the transcription and translation levels in Sprague Dawley (SD) rats supplemented with tempeh. A total of 6 female SD rats were divided into 3 groups of 2 rats. The first group was the control and was fed a standard diet without tempeh. The second- and third group were fed with a standard diet supplemented with raw and cooked tempeh, respectively. Ileum tissue samples were collected after tempeh supplementation for 28 days. RNA was extracted from ileum samples, and measurement of IgA gene expression was further analyzed using semi quantitative real-time PCR. The concentration of IgA protein was quantified from ileum lysate using the half sandwich ELISA method. IgA gene expressions in rats supplemented with raw, and with cooked tempeh, were 1.18 and 1.17 fold higher, respectively, compared to the control group. Moreover, IgA protein secretion levels also increased 2.46 and 2.08 fold, respectively, compared to the control group. The result of this study indicates that both raw and cooked tempeh may stimulate IgA secretion, and also that both viable and non-viable microorganisms might stimulate IgA gene expression.